The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1089/soro.2019.0040
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Multiaxial Shoulder-Motion Tracking Based on Flexible Resistive Sensors Applied to Exosuits

Abstract: This article describes the performance of a flexible resistive sensor network to track shoulder motion. This system monitors every gesture of the human shoulder in its range of motion except rotations around the longitudinal axis of the arm. In this regard, the design considers the movement of the glenohumeral, acromioclavicular, sternoclavicular, and scapulothoracic joints. The solution presented in this work considers several sensor configurations and compares its performance with a set of inertial measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 44 publications
0
19
0
1
Order By: Relevance
“…Others have sought to optimize sensor integration by investigating the minimal number of distributed sensors required to track multi‐DOF motion of the body, comparing to video‐based motion tracking system results as ground truths. [ 15,511 ] In a shirt that uses textile sensors to estimate shoulder kinematics, machine learning algorithms helped the researchers down‐select from eight to four sensors for motion tracking. [ 15 ] Regardless of the sensor architecture and underlying mechanism, choice of location of integration and sensor network design could benefit from experiment‐based studies when implemented into wearable robots.…”
Section: Textile Integration For Wearable Robotsmentioning
confidence: 99%
“…Others have sought to optimize sensor integration by investigating the minimal number of distributed sensors required to track multi‐DOF motion of the body, comparing to video‐based motion tracking system results as ground truths. [ 15,511 ] In a shirt that uses textile sensors to estimate shoulder kinematics, machine learning algorithms helped the researchers down‐select from eight to four sensors for motion tracking. [ 15 ] Regardless of the sensor architecture and underlying mechanism, choice of location of integration and sensor network design could benefit from experiment‐based studies when implemented into wearable robots.…”
Section: Textile Integration For Wearable Robotsmentioning
confidence: 99%
“…Using a configuration of seven one-axis sensors, as in previous work [21], it is possible to obtain 95% of the variance of the principal components for the shoulder gestures. The configuration proposed in this paper places only an array of four flexion sensors in the intermediate positions due to the fact that they provide flexion measurements in two axes.…”
Section: Methodsmentioning
confidence: 99%
“…It was proved that it is possible to obtain 95% of the variance of the main components for shoulder gestures with an array of seven single-axis resistive sensors [ 19 ]. Other results showed that it is possible to estimate the gestures of the shoulder with a performance 95.4% using an array of four WFSs and EMG signals [ 28 ].…”
Section: Previous Work By the Authorsmentioning
confidence: 99%
“…Initially, four sADS were placed in the intermediate positions of the seven single-axis resistive sensors configuration recommended by [ 19 ]. Replicating the proposed 20-layer hidden neural network method, with a configuration for the acquired data from the four sADS of [70%, 15%, 15%] for training, cross-validation and test stages, respectively, an overfitting was identified.…”
Section: Previous Work By the Authorsmentioning
confidence: 99%
See 1 more Smart Citation